The Business Diplomacy of Mayora Indah Ltd. on The Kopiko Brand Through Export to the Philippines and Promotions on Korean Dramas - Syahrul Salam; Mansur Juned; Rahmadini Agung Ayu Utami (RIRAI Publisher, 2023)
Diplomacy in business is needed to make market expansion activities more effective. This step by MNCs is then referred to as business diplomacy and also benefits the state because it can simultaneously become a means of diplomacy and achieve state interests. Mayora Indah Ltd. is a giant MNC from Indonesia that can dominate the global market. The success of Mayora Indah Ltd. in filling the global market can be seen in the popularity of Kopiko as their flagship product. This article aims to determine the strategies of business diplomacy taken by Mayora Indah Ltd to achieve the company's interests successfully. This article will then review the concepts related to business diplomacy proposed by Alammar & Pauleen (2016) as a foundation for analyzing the case study. This research finds that in the core knowledge competencies, Mayora Indah Ltd. applies internal knowledge through exposure to Kdrama producers related to Kopiko, with the aim that they can understand the product that will later be aired. Meanwhile, on multi-perspective consideration, Mayora Indah Ltd. invests in manufacturing in the Philippines and buys coconut commodities for environmental scanning.